Strategi Branding Program Studi Pendidikan Agama Islam dalam Membangun Identitas Akademik dan Citra Digital Perguruan Tinggi: Studi Kualitatif - Arif, Fadli Maulana; Junaidi, Junaidi (Lembaga Yasin AlSys, 2025)
Although higher education branding strategies have been widely examined in previous studies, research that specifically discusses the role of branding in shaping the academic identity and digital image of Islamic Religious Education study programs remains relatively limited. This study aimed to explore the branding strategies of the Islamic Religious Education Study Program in constructing its academic identity and strengthening the digital image of the university. The research employed a qualitative approach with a case study design, involving program leaders, lecturers, and students selected through purposive sampling. Data were collected through in-depth interviews, observations of academic activities and the study program’s digital media, and analysis of institutional documents, then analyzed using thematic analysis to identify emerging patterns and key themes. The findings show that the academic identity of the Islamic Religious Education Study Program is constructed through the integration of Islamic values with academic and professional competencies, as reflected in the curriculum, the implementation of the tridharma of higher education, and institutional narratives on digital media. Digital media, particularly the website and social media, play a strategic role in communicating academic identity and building institutional image, although challenges remain in maintaining message consistency and managing content. These findings underscore the importance of a clear academic identity, the active involvement of internal actors, and integrated digital branding management in enhancing the competitiveness and image of the Islamic Religious Education Study Program, while also offering theoretical contributions to the study of value-based higher education branding and practical implications for study program managers in designing sustainable branding strategies.